SCAFFOLDING DALAM PEMBELAJARAN MATEMATIKA - Wahyuning Retnodari; Widanty Faddia Elbas; Selvi Loviana (LINEAR: Journal of Mathematics Education, 2020)
In the term scaffolding itself can be interpreted that the word "scaffold" which is often used in building work, which is one of the temporary structures that help a job that can complete the work that is experiencing difficulties, so it cannot be done in the job. In this case scaffolding can help the achievement that cannot be solved individually. Then we can develop the term so that it can be said that one of the formation provided by the teacher or peer group, even his parents in supporting learning, in this case has a high ability factor that is owned by someone. In scaffolding the teacher is able to complete tasks or concepts in terms of learning that can be managed individually. In this case educators only provide skills in innovation or new knowledge from those who have been given assignments that are outside the area within the limits of students' learning abilities. In scaffolding mathematics learning in this case hopefully can make the formation of traits in learning better, so that in the process of building students can carry out their own, even have their own knowledge in learning. In this matter discussed are the notions of scaffolding, cognitive learning theory, the strengths and weaknesses of scaffolding, the learning method, the steps of the learning method and even the application of problem solving to mathematics. So that there is an alternative strategy implementation in the application of scaffolding which includes stages such as exploitation, reviewing, restructuring, and developing conceptual thinking. Therefore, this journal will discuss it all. Hopefully it can make the development of changes that support the process of learning mathematics at this time.